Analysis Of The Effect Of Inflation, Sbis, And Exchange Rates On Third Party Funds (DPK) For Islamic Banking In Indonesia - Khairiyah, Ririn (Universitas Muhammadiyah Sumatera Utara, 2022)
This Reasearch aim to know Analysis Of The Effect Of Inflation, Sbis, And Exchange Rates On Third Party Funds (DPK) For Islamic Banking In Indonesia, methods Classical Assumption Test, Normality Test, Autocorrelation Test. Hypothesis Test, Partial Test (t-test), F-Test Coefficient of Determination Test (R2). Then The Results are 1) Inflation has a negative effect on Islamic Banking Third Party Funds in Indonesia for the 2013-2018 period,2) SBIS has a positive and significant impact on Islamic Banking Third Party Funds in Indonesia for the 2013-2018 period, 3) Exchange rate has a positive and significant impact on Islamic Banking Third Party Funds in Indonesia for the 2013-2018 period, 4) nflation, SBIS and the exchange rate simultaneously have a significant effect on third party funds for Islamic banking in Indonesia for the 2013-2018 period.